Community-supported self-administered tuberculosis treatment combined with active tuberculosis screening: a pilot experience in Conakry, Guinea - Souleymane Hassane-Harouna; Tinne Gils; Tom Decroo; Nimer Ortuño-Gutiérrez; Alexandre Delamou; Gba-Foromo Cherif; Lansana Mady Camara; Leen Rigouts; Bouke Catherine de Jong (Taylor & Francis Group, 2023)
Directly observed treatment (DOT) for tuberculosis (TB) is recommended by the World Health Organization. However, DOT does not always meet patients' preferences, burdens health facilities, and is hard to implement in settings where access to healthcare services is regularly interrupted. A model addressing these limitations of DOT is community-supported self-administered treatment (CS-SAT), in which patients who self-administer TB treatment receive regular visits from community members. Guinea is a country with a high TB burden, recurrent epidemics, and periodic socio-political unrest. We piloted a CS-SAT model for drug-susceptible TB patients in Conakry, led by community volunteers, who also conducted active TB case finding among household contacts and referrals for isoniazid preventive treatment (IPT) in children below 5 years old. We aimed to assess TB treatment outcomes of patients on CS-SAT and describe the number of patients identified with TB case finding and IPT provision. Prospectively enrolled bacteriologically confirmed TB patients, presenting to two facilities, received monthly TB medication. Community volunteers performed bi-weekly (initiation phase) and later monthly (continuation phase) home visits to verify treatment adherence, screen household contacts for TB, and assess IPT uptake in children under five. Among 359 enrolled TB patients, 237 (66.0%) were male, and 37 (10.3%) were HIV-positive. Three hundred forty (94.7%) participants had treatment success, seven (1.9%) died, seven (1.9%) experienced treatment failure, and five (1.4%) were lost-to-follow-up. Among 1585 household contacts screened for TB, 26 (1.6%) had TB symptoms, of whom five (19.2%) were diagnosed with pulmonary TB. IPT referral was done for 376 children from 198 households. In a challenging setting, where DOT is often not feasible, CS-SAT led to successful TB treatment outcomes and created an opportunity for active TB case finding and IPT referral. We recommend the Guinean CS-SAT model for implementation in similar settings.